Prognostic significance of albumin-to-globulin ratio in patients with renal cell carcinoma: a meta-analysis - Mao, Huaying; Yang, Fan (Frontiers in Oncology, 2023)
Background: Whether the albumin-to-globulin ratio (AGR) predicts the prognosis of renal cell carcinoma (RCC) remains controversial. Herein, we performed a metaanalysis to critically evaluate the relationship between the AGR and RCC prognosis, as well the association between the AGR and the clinicopathological characteristics of RCC.The PubMed, Web of Science, Embase, and Cochrane Library databases were thoroughly and comprehensively searched from their inception until June 24, 2023.To determine the predictive significance of the AGR, hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) were calculated from pooled data. The relationship between the AGR and the clinicopathological features of RCC was evaluated by estimating odds ratios (ORs) and 95% CIs in subgroup analyses.The meta-analysis included nine articles involving 5,671 RCC cases. A low AGR significantly correlated with worse overall survival (OS) (HR = 1.82, 95% CI = 1.37-2.41, p <0.001) and progression-free survival (PFS) (HR = 2.44, 95% CI = 1.61-3.70, p <0.001). Analysis of pooled data also revealed significant associations between a low AGR and the following: female sex (OR = 1.48, 95% CI = 1.31-1.67, p <0.001), pT stage T3-T4 (OR = 4.12, 95% CI = 2.93-5.79, p <0.001), pN stage N1 (OR = 3.99, 95% CI = 2.40-6.64, p <0.001), tumor necrosis (OR = 3.83, 95% CI = 2.23-6.59, p <0.001), and Fuhrman grade 3-4 (OR = 1.82, 95% CI = 1.34-2.42, p <0.001). The AGR was not related to histology (OR = 0.83, 95% CI = 0.60-1.15, p = 0.267).In patients with RCC, a low AGR strongly predicted poor OS and PFS and significantly correlated with clinicopathological features indicative of disease progression.